Experimental evaluation of the impacts of considering inherent response characteristics for lighting technologies in building energy modeling - Ozenc, S.; Uzunoglu, M.; Guler, O. (ELSEVIER SCIENCE SA, 2014)
Lighting has become a leading necessity for sustaining the life quality of humankind since the first produced lighting equipments. Even the available softwares for modeling the performance and energy related characteristics of the light sources provide a significant insight for the best and programmed utilization of lighting systems; there are some drawbacks of these commonly utilized softwares. These software tools generally consider the energy performance of light sources directly proportional to dimming without employing a detailed energy profile for different light sources even each different source has a specific characteristics to dimming levels. This assumption may provide significant discrepancies if the energy modeling softwares and real time operating results are compared and accordingly may reduce the performance of the energy modeling software. Thus, response characteristics of two of the mostly utilized light sources - fluorescent and LED technologies - are experimentally examined in terms of response characteristics to different dimming levels. Besides, a sample office lighting system is analyzed in order to better present the discrepancies between experimentally derived response characteristics of the mentioned light sources and energy modeling software based results. It is shown that considering the inherent response characteristics of each light source technology promotes the performance of a modeling approach compared to assuming common response characteristics for every light source technologies. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Dimming; Energy modeling software; Fluorescent; LED; Lighting; CONTROL-SYSTEMS; PERFORMANCE; OFFICES; Construction & Building Technology; Energy & Fuels; Engineering